2000
DOI: 10.1161/01.hyp.35.1.319
|View full text |Cite
|
Sign up to set email alerts
|

eNOS Mediates l -Arginine–Induced Inhibition of Thick Ascending Limb Chloride Flux

Abstract: Abstract-We recently reported that the rat thick ascending limb (THAL) possesses an active isoform of nitric oxide synthase (NOS) that is substrate-limited in vitro. NO produced by THAL NOS inhibits chloride flux. Protein and transcript for each of the primary NOS isoformsϪendothelial (eNOS), inducible (iNOS), and neuronal (nNOS)Ϫhave been demonstrated in THALs. However, the NOS isoform that mediates NO-induced inhibition of chloride flux is unknown. We hypothesized that NO produced from eNOS in the THAL inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(83 citation statements)
references
References 30 publications
0
83
0
Order By: Relevance
“…However, in some cells Very little is known about the role of PI3-kinase-stimulated eNOS activity along the nephron and its role in regulating salt and water reabsorption. Previous data from our laboratory showed that eNOS-derived NO inhibits NaCl absorption by the THAL (35,38) and that NO produced in this nephron segment acts in a paracrine manner to modulate tubuloglomerular feedback (TGF) (52). We have also reported that hormones that inhibit NaCl absorption by the THAL may do so by activating the PI3-kinase/eNOS pathway (37).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…However, in some cells Very little is known about the role of PI3-kinase-stimulated eNOS activity along the nephron and its role in regulating salt and water reabsorption. Previous data from our laboratory showed that eNOS-derived NO inhibits NaCl absorption by the THAL (35,38) and that NO produced in this nephron segment acts in a paracrine manner to modulate tubuloglomerular feedback (TGF) (52). We have also reported that hormones that inhibit NaCl absorption by the THAL may do so by activating the PI3-kinase/eNOS pathway (37).…”
Section: Discussionmentioning
confidence: 94%
“…Hsp90 is necessary for eNOS translocation to the apical membrane in response to increased luminal flow. Given the importance of eNOS-derived NO in the regulation of THAL NaCl absorption (35,38) and the role of eNOS in various physiological processes in epithelial cells of the respiratory tract, brain, and testis (14,29,55,57,60), this mechanism is likely to play an essential role in the regulation of NO levels in these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 NOS 3 is responsible for autocrine inhibition of NaCl absorption in the thick ascending limb. 28 We showed that NOS 3 function could be restored selectively to this segment of NOS 3 knockout mice using an adenovirus with a tissue-specific promoter. 13 Because we were able to transduce Ϸ75% to 95% of thick ascending limbs in vivo, we are now studying the specific role of the medullary thick ascending limb NOS 3 in the regulation of salt and water excretion in vivo.…”
Section: Roles For Renal Nomentioning
confidence: 95%
“…However, other studies, albeit not involving renal cell‐specific gene targeting, have suggested that nephron NOS3 may be an important modulator of renal salt handling and BP. l ‐arginine‐induced inhibition of transepithelial Cl − flux was abolished in TAL from global NOS3 KO mice, but not from global NOS1 or NOS2 KO mice 9. Further, NOS3 gene transfer into TAL of NOS3 KO mice restored l ‐arginine‐induced inhibition of NaCl reabsorption 10.…”
Section: Introductionmentioning
confidence: 91%